PEMBELAJARAN NEUROSAINS DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK PADA PONDOK PESANTREN - Erniati Erniati (State Institute of Islamic Studies (IAIN) Palu, 2015)
Learning neuroscience offers an alternative to the development of intelligence potential learners linguistic and logical through physical movement, rohamiah, physical, interpersonal, intrapersonal, naturalist and existential. The learning system includes morality codes of learners are packed in Islamic boarding school education curriculum with teaching presentation of cognitive, affective and psychomotor. Islamic education boarding school curriculum neurosains apply learning methods for the development of intellect learners so in the formation of character can maximize the performance of sense. In neuroscience of learning, students are given the opportunity to actively construct knowledge through learning. Thus, neuroscience learning combined with a variety of disciplines so integrated into the mainstream of the formation of character.